Functional and Antigenic Antithrombin III Values in Plasma and Serum from 115 Regular Blood Donors and Antithrombin III In Prediction of Postoperative Thrombosis - Nilsen, D W T; Jeremic, M; Weisert, O K; Fønstelien, E; Godal, H C (Thrombosis and Haemostasis, 1983)
Antithrombin III (AT-III) was determined functionally using chromogenic substrate (S-2238) and immunologically using radial immunodiffusion (RID) in plasma and serum from 115 blood donors. There was a decrease in functional activity by 43.5% and in antigen concentration by 18.4% during in vitro coagulation when corresponding serum and plasma samples were compared. A positive correlation was found between the two methods in plasma (r=0.784) as well as in serum (r = 0.658). RID in serum correlated well with RID in plasma (r = 0.811), but the correlation for S-2238 in plasma and serum was poor (r = 0.411). Functional AT-III decrease during coagulation was uncorrelated with age and fibrinogen, and was not statistically affected by sex, smoking or blood groups.Preoperative functional AT-III activity was measured in 25 patients undergoing elective hip replacement, 60% of whom developed postoperative thrombosis. The functional activity in serum discriminated well between the thrombotic and nonthrombotic group of patients (p<0.025), whereas the activity in plasma showed only a minor difference.
Keywords: Plasma-antithrombin III; Serum-antithrombin III; Post-operative thrombosis